The influence of ethanol consumption on a course of endometriosis - Monika Kopec; Paula Szlendak; Jan Kotarski; Marek Gogacz (Ginekologia Polska)
OBJECTIVES: Due to the increasingly faster pace of life and responsibilities, stress has become an integral part of daily life. Every year, numerous social campaigns in the media raise the issue of increasing alcohol consumption. Endometriosis is a chronic, causally incurable, estrogen-dependent and inflammatory gynecological disorder, described as presence of ectopic endometrial tissue outside the uterine cavity. Some studies suggest that alcohol may aggravate the symptoms of the disease. The aim of the study is to present a comprehensive review reffering to the role of ethanol in the course of endometriosis. MATERIAL AND METHODS: A review of the literature available in the PubMed database between 2000 and 2024 was conducted, using the following keywords: “endometriosis”, “alcohol”, “ethanol”. The search included articles published in English. Publications without full text access and duplicates were rejected. 247 records were screened of which 15 met the eligilibity criteria, and 12 were included in this article. RESULTS: Alcohol may affect estrogen production (by increasing the activity of aromatase and interacting with luteinizing hormone), promotes pro-inflammatory pathways and oxidative stress. It is also perceived as a form of self-management therapy resulting from pain, anxiety, and low self-esteem. Patients who are alcohol-dependent more often experience infertility, miscarriages, anovulation and ovarian pathologies. CONCLUSIONS: Although there is no clear evidence suggesting the adverse effect of ethanol on the course of endometriosis, the substance may be life-destroying in alcohol-dependent women. It may cause more severe course of endometriosis affecting many ascpectcts of life.